ANALYSIS OF INCLUSIVE ECONOMIC GROWTH IN MANOKWARI REGENCY - Pasaribu, Sandi Hasudungan (Penelitian dan Pengembangan Ilmu, 2025)
Inclusive economic growth emphasizes not only economic expansion but also the equitable distribution of development benefits across society. This study aims to analyze the inclusiveness of economic growth in Manokwari Regency over the period 2016–2025. Inclusive growth is assessed by examining the relationship between economic growth and key welfare indicators, namely poverty, unemployment, and income inequality. This study employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS) of Manokwari Regency. The data include Gross Regional Domestic Product (GRDP) at constant prices, poverty rate, open unemployment rate, and Gini ratio. The analytical method used is the Inclusive Growth Index (IGI). The results indicate that although Manokwari Regency experienced positive economic growth during the study period, the growth has not been fully inclusive. Economic growth has not consistently reduced poverty, unemployment, and income inequality. These findings suggest the need for development policies that prioritize employment creation, poverty reduction, and income distribution to ensure that economic growth benefits all segments of society.